F. Dostoevsky’s Literary Text in the Context of Intercultural Communication (Eurasian Journal of Philology Science and Education, 2025)
The purpose of the article is to study the artistic heritage of F. Dostoevsky in the aspect of the problem of intercultural communication, which is very relevant for modern philological science. The main scientific idea is that when you come into contact with a foreign language culture, there is a moment of national identification, a different dimension of self-awareness, as a result of which the reader's interest is actualized. The article examines F. Dostoevsky's view of European civilization in the guise of Germany both in retrospect and at his present stage, his vision of the trajectory of historical and cultural mutual influence between Europe and Russia, as well as his definition of the German mentality and the psychotype of the Russian person reflected in his literary texts. During the work on the topic, the method of receptive aesthetics, as well as the methodology of hermeneutics and the historical and literary method were used to substantiate the reliability of the results, conclusions and provisions. The scientific significance of the work lies in the fact that its results can serve for further research of the problem of intercultural communication on the new material of creativity of foreign and Kazakhstani authors. The practical significance of the research is seen in the possibility of its use in the teaching and scientific activities of philologists. In the course of the conducted research, it is concluded that in the works of art F. Dostoevsky provides an in-depth analysis of the general trajectory of European development in the projection of the image of Germany and the German world as a whole. The use of a contrasting foreign background underscores the sharp contrast between the Russian character marked by irrationality, passion, and unpredictability and Western rationality. Yet a paradox emerges: Dostoevsky’s characters reject Western “virtue” grounded in mercantilism and the accumulation of capital but offer no constructive alternative beyond the pursuit of unlimited freedom and the rejection of reason. But, nevertheless, the literary works of F. Dostoevsky's concept of the incompleteness of Russian nature, its ability to combine many opposites and its potential for its own national evolution in accordance with universal humanistic ideals is fully confirmed.Keywords: intercultural communication, the concept of pan-European development, foreign language cultural environment, national worldview, personality psychotype.